Simulation on microgrid connected PV system under balance and unbalance fault - Ameerul A. J. Jeman; Naeem M. S. Hannoon; Nabil Hidayat; Mohamed M. H. Adam; Ismail Musirin; Vijayakumar V (Institute of Advanced Engineering and Science, 2019)
This paper presents an analysis in Matlab/Simulink of a three-phase photovoltaic system under balance and unbalance faults in Matlab/Simulink. The aim of this paper is to investigate the performance of the system under various types of fault. The simulation involved various types of faults occurring at different distances from the point of common coupling of the PV system. This paper also aimed to identify what type of fault that may severely damage the system. The simulation results presented in this paper show that the three-phase fault in the microgrid was severely affecting the system since it involved all the three phases of the system while the distance of the fault occurrence is less influenced in the system. The purpose of this research is to observe the effect on the system based on the types of faults occur and the distance faults occur.